REKAYASA BIOKONVERSI LIMBAH CAIR INDUSTRI PANGAN MENJADI PLASTIK BIODEGRADABLE DENGAN MENGGUNAKAN LUMPUR AKTIF - Wikanta, Deddy Kurniawan; Yulianto, Mohamad Endy; Arifan, Fahmi (METANA, 2007)
Abstract Plastics waste has a negative effect on our environment. one effort to solve a  problem exerted in plastic waste is by making a degradable plastic material. Polihidroksialkanoat (PHA) is one of biodegradable plastic material which is include in the polyester group. PHA can be completely degraded and has  similar properties. with conventional plastic. The usage of liquid food industry waste is a good alternative for the production of PHA, since liquid waste of food industry comprise of organics substance such as C, H, O, N and  S. The production of Polihidroksialkanoat (PHA) from liquid waste of flour industry, wasconducted in a of sequencing batch reactor (SBR).The objectives  of this research are to study the effect of batch time in one cycle of sequencing batch reactor(SBR), to compare between short and ordinary cycle in SBR system to PHA accumulation and kind of PHA, to study optimum condition of producing PHA. The first experimen was done In time of less than 12 hours by using filling time  variable and ratio of duration of Aerob and anaerob process. The constand conditions were ambient temperature and neutral pH (at the begining). The results shows that at running with time ratio of aerob:anaerob was 6:3 hours and a  same duration of  feeding, the highest average PHA content was got at the run when filling step is in six hours anaerob with aerob breaking time. The feeding duration  also influence the PHA formation. the short feeding duration yielded the highest average PHA content. An average PHA 0.1838 g/gsel was yielded at two hours feeding duration   Key Words :biodegradable:plastic:waste